IDENTIFIKASI JENIS KAYU PERDAGANGAN DAN KURANG DIKENAL YANG DIPERDAGANGKAN DI DKI JAKARTA - Sri Rulliaty; Nenny Sumarliani (Jurnal Penelitian Hasil Hutan, 1991)
A survey on wood species marketed in the Jakarta Meb'opolitan has.  been conducted and the reault reporled in this paper. The result shows that there are all together 35 wood grouping available• in the market. Each group consiiitedof one or more species with similar (or almost) colour, density and pore density.